Brief family history questionnaire to screen for Lynch syndrome in women with newly diagnosed non-serous, non-mucinous ovarian cancers. Issue 7 (10th January 2022) - Kim, Soyoun Rachel; Tone, Alicia; Kim, Raymond; Cesari, Matthew; Clarke, Blaise; Hart, Tae; Aronson, Melyssa; Holter, Spring; Lytwyn, Alice; Maganti, Manjula; Oldfield, Leslie; Gallinger, Steven; et al.
Abstract : Objectives: While ovarian cancer is the third most common Lynch syndrome-associated cancer in women, there is no established screening strategy to identify Lynch syndrome in this population. The objective of this study was to assess whether the 4-item brief Family History Questionnaire can be used as a screening tool to identify women with ovarian cancer at risk of Lynch syndrome. Methods: In this prospective cohort study, participants with newly diagnosed non-serous, non-mucinous ovarian cancer completed the brief Family History Questionnaire, extended Family History Questionnaire, and had tumors assessed with immunohistochemistry for mismatch repair proteins, MLH1 methylation, and microsatellite instability testing. All underwent universal germline testing for Lynch syndrome. Performance characteristics were compared between the brief Family History Questionnaire, extended Family History Questionnaire, immunohistochemistry± MLH1 methylation, and microsatellite instability testing. Results: Of 215 participants, 169 (79%) were evaluable with both the brief Family History Questionnaire and germline mutation status; 12 of these 169 were confirmed to have Lynch syndrome (7%). 10 of 12 patients (83%) with Lynch syndrome were correctly identified by the brief Family History Questionnaire, compared with 6 of 11 (55%) by the extended Family History Questionnaire, 11 of 13 (85%) by immunohistochemistry± MLH1 methylation, and 9 of 11 (82%) by microsatellite instability testing. The sensitivity, specificity, positive predictive values, and negative predictive values of the brief Family History Questionnaire were 83%, 65%, 15%, and 98%, respectively. A combined approach with immunohistochemistry and the brief Family History Questionnaire correctly identified all 12 patients with Lynch syndrome. The brief Family History Questionnaire was more sensitive than the extended Family History Questionnaire and took <10 min for each patient to complete. Conclusions: The brief Family History Questionnaire alone or combined with immunohistochemistry may serve as an adequate screening strategy, especially in centers without access to universal tumor testing.